Współpraca Sądu Konstytucyjnego Federacji Rosyjskiej z Europejskim Trybunałem Praw Człowieka w latach 1998-2022 - Czachor, Rafał (PRAWO i WIĘŹ, 2024)
The following paper aims to highlight two periods of cooperation between the Russian Constitutional Court and the European Court of Human Rights. Special attention is paid to the legal mechanisms adopted by the Constitutional Court in order not to implement the decisions of the European Court. The Constitutional Court of Russia expressed the thesis that international treaties and decisions of the international court are subordinate to the Constitution in the hierarchy of sources of law. This was subsequently confirmed by the amendments to the Law on the Constitutional Court and the Constitution of Russia. In 2022, Russia lost its membership in the Council of Europe and abandoned the European legal order. There is no doubt that in the Russian Federation the status of international treaties, including the European Convention on Human Rights, depends on the political situation in the country and the attitude of the Russian authorities to cooperation with the international community.